An evaluation on SP surface property by means of combined FEM-DEM shot dynamics simulation. (January 2018) - Zhang, Jiabin; Lu, Shihong; Wu, Tianrui; Zhou, Zhen; Zhang, Wei
Highlight: The FEM analysis was validated as a reliable way for predicting indentation radius. A coverage prediction based on FEM-DEM simulation was developed and validated. The area ratio calculation for coverage was compared with classical equation. A statistical study about influence of SP processing parameters on the coverage rate was conducted. The DEM simulation generates an input file for FEM simulation, which is then used to analyse the CRS and resulting roughness corresponding to SP parameters. Abstract: The surface coverage induced by shot peening (SP) has substantial influence on the fatigue durability of components. The underlying motivation for this work was to predict coverage, compressive residual stress (CRS), and roughness of the alloy, Al 2024-T351. These characteristics were assessed by computational modelling that is based on a combined finite element method (FEM) and discrete element method (DEM). The advantage of this combined method is that we only need to combine a representative dimple with the impact locations obtained from different SP parameters in DEM. Especially in the parametric analysis was carried out to evaluate coverage regarding to SP parameters. Furthermore, the DEM simulation generates an input file for the FEM simulation, which is then used to analyse the CRS and the resulting roughness that corresponds to SP parameters. The numerical coverage study (based on the combined DEM-FEM method) exhibited the same trend as the experimental data, with respect to the percentage of full coverage time, t, and is more reliable than theoretical calculations. In a practical sense, the developed model has the ability to accurately achieve the desired surface with the ability to adjust the SP parameters efficiently.